2017
DOI: 10.1097/dcr.0000000000000759
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Efficacy of Polyethylene Glycol With Ascorbic Acid and an Oral Sulfate Solution in a Split Method for Bowel Preparation: A Randomized, Multicenter Phase III Clinical Trial

Abstract: Oral sulfate solution is effective at colonoscopy cleansing and has acceptable tolerability when it is compared with polyethylene glycol with ascorbic acid. The taste and flavor of oral sulfate solution still need to be improved to enhance tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…This paper focused on the effectiveness of the formulation, not the safety. This study supports previous studies [13][14][15]28 that showed the non-inferiority of OSS compared with PEG-AA. Interestingly, OSS may be of benefit for older patients and female patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This paper focused on the effectiveness of the formulation, not the safety. This study supports previous studies [13][14][15]28 that showed the non-inferiority of OSS compared with PEG-AA. Interestingly, OSS may be of benefit for older patients and female patients.…”
Section: Discussionsupporting
confidence: 92%
“…Concurrently, several randomized clinical trials have shown that OSS has comparable or better outcomes than PEG formulations and has acceptable safety. [14][15][16] Thus, this observational study aimed to compare the efficacy of OSS and PEG-AA and to identify the patient characteristics that were favorable to certain formulations.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis better reflects the real-world cleansing performance of NER1006 versus current alternatives such as 2LPEG (MOVIPREP ® , Norgine Ltd, Harefield, UK; assessed in the MORA trial) and oral sulfate solution (OSS; SUPREP ® , Braintree Laboratories, Braintree, MA, USA; assessed in the NOCT trial). These two comparators are both widely used and known for their high cleansing efficacy [23][24][25][26][27]. For a robust assessment of comparative cleansing efficacy, three complementary efficacy measures were analyzed: first, the patient-level rates of standard HCS overall colon cleansing success; then, the patient-level rate of overall high-quality cleansing; finally, the rate of segments cleansed at high-quality across the patient population ('population-level').…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was performed by study. Because 2LPEG and OSS have between them shown a comparable cleansing efficacy in two recent randomized controlled trials, the NOCT and MORA data sets were combined for an analysis of combined NER1006 versus combined 2LPEG/OSS [31,32]. Hereafter, combined NER1006 and combined 2LPEG/OSS will simply be referred to as NER1006 and 2LPEG/ OSS, respectively.…”
Section: Assessmentsmentioning
confidence: 99%